2010
DOI: 10.1152/ajpcell.00251.2009
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological properties of human induced pluripotent stem cells

Abstract: Human embryonic stem cells (hESCs) can self-renew while maintaining their pluripotency. Direct reprogramming of adult somatic cells to induced pluripotent stem cells (iPSCs) has been reported. Although hESCs and human iPSCs have been shown to share a number of similarities, such basic properties as the electrophysiology of iPSCs have not been explored. Previously, we reported that several specialized ion channels are functionally expressed in hESCs. Using transcriptomic analyses as a guide, we observed tetraet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 27 publications
5
41
0
1
Order By: Relevance
“…Embryonic stem cells differentiate in vitro into spontaneously beating multicellular cardiomyocyte clusters within embryoid bodies (EBs), while recapitulating developmental stages of embryonic cardiomyogenesis (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Thus, human embryonic stem cell-derived cardiomyocytes (hESC-CMs) may provide insights into the pacemaker mechanisms of embryonic cardiac development.…”
mentioning
confidence: 99%
“…Embryonic stem cells differentiate in vitro into spontaneously beating multicellular cardiomyocyte clusters within embryoid bodies (EBs), while recapitulating developmental stages of embryonic cardiomyogenesis (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Thus, human embryonic stem cell-derived cardiomyocytes (hESC-CMs) may provide insights into the pacemaker mechanisms of embryonic cardiac development.…”
mentioning
confidence: 99%
“…In particular, several voltagegated currents, including depolarization-activated K + (Kv), hyperpolarization-activated cation (HCN), and T-type Ca 2+ currents, have been measured in one or both species of ESCs (Wang et al, 2005;Sartiani et al, 2007;Jiang et al, 2010Kleger et al, 2010Lau et al, 2011;Ng et al, 2010;Rodriguez-Gomez et al, 2012). In comparative studies, significantly larger (5 fold)…”
Section: Discussionmentioning
confidence: 99%
“…Kv currents were recorded in hESC compared with mESC (Wang et al, 2005; but see also Jiang et al, 2010) but for HCN currents, they were detected in mESCs but not in hESCs. Our 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 4...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-specific pluripotent cell lines may provide a limitless source for human cell therapeutic application. However, although human ES cells and human iPS cells have been shown to share a number of similarities, there are still differences electrophysiology properties between human ES cells and human iPS cells (Jiang et al, 2010). It has been showed that foreign genes were silenced or removed after reprogramming, but those approaches have low reprogramming efficiency, and either leave residual vector sequences, or require tedious steps.…”
Section: The Derivation Of Embryonic Stem (Es) Cells and Induced Plurmentioning
confidence: 99%